Pemanfaatan Teknologi Informasi Untuk Meningkatkan Pembelajaran Pendidikan Agama Islam di MI/SD - Munawir; Khoiriyatin, Vilda Zahrotul; Ayu Dwi Rahmawati (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2024)
This study aims to explore the utilization of information and communication technology in learning Islamic Religious Education in Elementary/Madrasah Ibtidaiyah (SD/MI). Through literature research method. Data analysis was conducted using the Miles and Huberman data analysis model. Qualitative analysis activities are carried out interactively and continuously until they reach an adequate point. The steps taken include data reduction, data presentation, and conclusion verification. This research explains the definition of information and communication technology, the utilization of information and communication technology in learning Islamic religious education, its positive and negative impacts, and examples of information and communication technology devices in learning Islamic religious education. The use of information and communication technology in learning Islamic religious education can expand access to education, increase administrative efficiency, and improve the quality of learning. However, keep in mind that the use of information and communication technology must be balanced with an understanding of appropriate and ethical use and careful supervision. The utilization of information and communication technology in Islamic learning can increase the effectiveness and efficiency of learning, but it also requires wise management. Thus, the utilization of technology and information used must still pay attention to the holistic aspects of education and the development of student character as a whole.